1958
DOI: 10.1182/blood.v13.6.589.589
|View full text |Cite
|
Sign up to set email alerts
|

Calcium-Lipid Complexes in Human Platelets

Abstract: Carefully washed human platelets contain calcium in an unusual state of chemical combination. Platelet calcium is non-ionic and is not exchangeable with ionic Ca45. On extraction of platelets with lipid solvents, the calcium separates with the phospholipids. The calcium-lipid complex thus obtained does not undergo any exchange with radioactive calcium. Study of other properties of platelets reveals that the clot-promoting activity of platelets (activated by antihemophilic factor and plasma thromboplastin compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
2
0

Year Published

1959
1959
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(5 citation statements)
references
References 17 publications
3
2
0
Order By: Relevance
“…On the other hand, Zn, Ca and Mg are present in platelets at easily measured levels. The Zn values agree closely with those determined by Foley et al (1968) (0.20-0.45, mean 0.29 [tg/1 0 9 platelets) but the values for Ca are considerably lower than those reported in the earlier work of Wallach et al (1958) who found the equivalent of 12.8 [tg/10 9 platelets. Skaer (1975 b) has examined human platelets using quantitative microprobe analysis and found that 1.99-2.61 mg Ca/g dry weight are found in the dense bodies; this lies within the range reported by Cousin and Caen (1964).…”
Section: Discussionsupporting
confidence: 89%
“…On the other hand, Zn, Ca and Mg are present in platelets at easily measured levels. The Zn values agree closely with those determined by Foley et al (1968) (0.20-0.45, mean 0.29 [tg/1 0 9 platelets) but the values for Ca are considerably lower than those reported in the earlier work of Wallach et al (1958) who found the equivalent of 12.8 [tg/10 9 platelets. Skaer (1975 b) has examined human platelets using quantitative microprobe analysis and found that 1.99-2.61 mg Ca/g dry weight are found in the dense bodies; this lies within the range reported by Cousin and Caen (1964).…”
Section: Discussionsupporting
confidence: 89%
“…Nor was the platelet release reaction affected by Bat ', which substitutes for Ca" and induces secretion from chromaflin cells (Douglas & Rubin 1964), or by bradykinin (Bygdeman & Hamberg (1969), which has been shown to evoke medullary secretion by depolarizing chromaffin cells and promoting inward movement of Ca (Douglas 1968). Direct measurements of platelet radioactivity following incubation with 4;1Ca++ demonstrated that only a very small fraction of added radioactivity could be extracted from the platelets, indicating that exogenous Ca" does not exchange with endogenous Ca", which is in accordance with the result reported by Wallach et al (1958). Induction of a release reaction by addition of collagen in the presence of external 45Ca++ was not followed by any increase in platelet 45Cat + radioactivity, further indicating that uptake of Ca" was not a necessary preroquisite for the release reaction.…”
supporting
confidence: 90%
“…Gaby and co-workers (Gaby, Hadley & Kaminski, 1957;Gaby, Naughton & Logan, 1959;Gaby & Silberman, 1960;Gaby et al 1960a, b;Silberman & Gaby, 1961) have suggestedthatphospholipid-amino acidcomplexes are concerned in transport processes. A similar suggestion has been made by Wallach, Surgenor & Steele (1958). The bean-leaf experiments measure transport processes in thatvaline must find its way to the site of protein synthesis.…”
Section: Discussionsupporting
confidence: 65%